Pulmonary embolism response teams: Purpose, evidence for efficacy, and future research directions. Issue 3 (9th June 2019) - Rosovsky, Rachel; Zhao, Ken; Sista, Akhilesh; Rivera‐Lebron, Belinda; Kabrhel, Christopher
Abstract : Abstract: Pulmonary embolism (PE) is a major cause of morbidity and mortality in the United States. Although new therapeutic tools and strategies have recently been developed for the diagnosis and treatment of patients with PE, the outcomes for patients who present with massive or high‐risk PE remain dismal. To address this crisis, pulmonary embolism response teams (PERTs) are being created around the world in an effort to immediately and simultaneously engage multiple specialists to determine the best course of action and coordinate the clinical care for patients with acute PE. The scope of this review is to describe the PERT model and purpose, present the structure and organization, examine the available evidence for efficacy and usefulness, and propose future directions for research that is needed to demonstrate the value of PERT and determine if this multidisciplinary approach represents a new standard of care.